2014
DOI: 10.1021/nn501787v
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Chains of Ferromagnetic Nanoparticles

Abstract: We report the fabrication of flexible chains of ferromagnetic Ni nanoparticles that possess the ability to adapt other than the typically observed rigid (nearly) straight configurations in the absence of an external magnetic field. The dynamic mobility of the ferromagnetic chains originates from a layer of densely grafted polyethylene glycol macromolecules enveloping each nanoparticle in the chain. While ferromagnetic chains of unmodified Ni nanoparticles behave as stiff nickel nanorods, the chains made of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Previous reports showed that magnetic induction [4] and external coating by induced self-assembly [5] are two effective methods for forming magnetic nanochains with nanoparticles. For microscopic systems, the size of the magnetic stirrer must be within nanoscale.…”
mentioning
confidence: 99%
“…Previous reports showed that magnetic induction [4] and external coating by induced self-assembly [5] are two effective methods for forming magnetic nanochains with nanoparticles. For microscopic systems, the size of the magnetic stirrer must be within nanoscale.…”
mentioning
confidence: 99%
“…Theoretical analysis and experiments revealed that the field-induced aggregation process of dipolar particles is a complex phenomenon and the structure of aggregates depends on the balance of magnetic forces, thermal fluctuations and other interaction mechanisms between NPs. NPs in the aggregates may undergo rearrangements [21][22][23][24] . The dynamics of the aggregates facilitates an increased efficiency of biocatalytic reactions in the nanocompartments generated in the aggregates.…”
Section: Nature Catalysismentioning
confidence: 99%
“…Several interesting phenomena are known for ferromagnetic filaments -in the AC magnetic field with a frequency high enough they orient perpendicularly to the field [5]. When magnetic field direction is changed, filaments form snake like 'S' shape [6]. If the direction is inverted, ferromagnetic filament makes a loop [7], which further relaxes by 3D motion.…”
Section: Introductionmentioning
confidence: 99%